Analysis of L-strip proximity fed rectangular microstrip antenna for mobile base station - Meahram M.K. (My University, 2025)
A wide-band L-strip proximity fed rectangular microstrip antenna is proposed and investigated both theoretically and experimentally. The radiating patch is located about 0.1λ0 (16.5 mm) above the ground plane. The broadband characteristic of antenna is achieved by employing a thick substrate (0.1λ0). Numerical results for the input impedance, VSWR, and co- and cross-polar radiation pattern are presented and compared with the measured results. Good agreement is obtained between computed and measured results. The effects of the geometric parameters of the L-strip like length of the vertical and horizontal portion of the strip are investigated. It is found that the antenna attains 48.36% impedance bandwidth (SWR ≤ 2) (theoretically) and 56.67% (experimentally) for optimized antenna design. The H-plane cross-polarization level is quite high (-16 dB) especially at (computed θ ≈ 60°, and measured θ ≈ 40°) whereas the E-plane cross-polarization level is very low. © 2007 Wiley Periodicals, Inc.